Reading between the Lines: Utilizing RNA-Seq Data for Global Analysis of sRNAs in Staphylococcus aureus - Hailee M. Sorensen (American Society for Microbiology, 2020)
ABSTRACT Regulatory small RNAs (sRNAs) are known to play important roles in the Gram-positive bacterial pathogen Staphylococcus aureus; however, their existence is often overlooked, primarily because sRNA genes are absent from genome annotation files. Consequently, transcriptome sequencing (RNA-Seq)-based experimental approaches, performed using standard genome annotation files as a reference, have likely overlooked data for sRNAs. Previously, we created an updated S. aureus genome annotation file, which included annotations for 303 known sRNAs in USA300. Here, we utilized this updated reference file to reexamine publicly available RNA-Seq data sets in an attempt to recover lost information on sRNA expression, stability, and potential to encode peptides. First, we used transcriptomic data from 22 studies to identify how the expression of 303 sRNAs changed under 64 different experimental conditions. Next, we used RNA-Seq data from an RNA stability assay to identify highly stable/unstable sRNAs. We went on to reanalyze a ribosome profiling (Ribo-seq) data set to identify sRNAs that have the potential to encode peptides and to experimentally confirm the presence of three of these peptides in the USA300 background. Interestingly, one of these sRNAs/peptides, encoded at the tsr37 locus, influences the ability of S. aureus cells to autoaggregate. Finally, we reexamined two recently published in vivo RNA-Seq data sets, from the cystic fibrosis (CF) lung and a murine vaginal colonization study, and identified 29 sRNAs that may play a role in vivo. Collectively, these results can help inform future studies of these important regulatory elements in S. aureus and highlight the need for ongoing curating and updating of genome annotation files. IMPORTANCE Regulatory small RNAs (sRNAs) are a class of RNA molecules that are produced in bacterial cells but that typically do not encode proteins. Instead, they perform a variety of critical functions within the cell as RNA. Most bacterial genomes do not include annotations for sRNA genes, and any type of analysis that is performed using a bacterial genome as a reference will therefore overlook data for sRNAs. In this study, we reexamined hundreds of previously generated S. aureus RNA-Seq data sets and reanalyzed them to generate data for sRNAs. To do so, we utilized an updated S. aureus genome annotation file, previously generated by our group, which contains annotations for 303 sRNAs. The data generated (which were previously discarded) shed new light on sRNAs in S. aureus, most of which are unstudied, and highlight certain sRNAs that are likely to play important roles in the cell.